Final act : a Lambert & Hook police procedural - Gregson, J. M. (Gregson, J. M. Lambert and Hook mysteries., 2016)
"Sam Jackson is not a man who suffers fools - or anyone else - gladly. A successful British television producer who fancies himself as a Hollywood mogul, he makes enemies easily, and delights in the fact. It is no great surprise that such a man should meet a violent death. Detective Chief Superintendent Lambert and Detective Sergeant Hook deduce that the person who killed him is almost certainly to be found among the company of actors who are shooting a series of detective mysteries in rural Herefordshire. But these are people who make a living by acting out other people's fictions, people more at home with make-believe than real life - and the two detectives find interrogating them a difficult business. How can Lambert and Hook fight their way to the truth when faced with a cast of practised deceivers?"--Jacket flap.